Facts on Growing and Use of Eucalyptus in Kenya - Oballa, P.O.; Konuche, P.K.; Muchiri, M.N.; Kigomo, B.N. (Kenya Forestry Research Institute, 2010)
Eucalypts are the most widely cultivated forest trees in the world. The genus Eucalyptus comprises more than 900 species and various hybrids and varieties. Most eucalypts occur naturally in Australia. In Kenya, eucalypts were introduced in 1902 to provide fuelwood for the Kenya-Uganda railway. Currently, eucalypts are used for fuelwood, timber, plywood, transmission poles, pulp, building materials, fencing posts, windbreaks and ornamentals. Eucalypts are grown in most ecological zones in Kenya and on a variety of soils, including infertile sands and heavy clays. The total area under eucalypts in Kenya is about 100,000 ha distributed in gazetted forests and land owned by large private companies, small-scale farmers and local authorities. The area under Eucalyptus is likely to increase as a result of the high demand for transmission poles to cater for the ongoing expansion in rural electrification and for construction, fuelwood, carbon sequestration and mitigation of the effects of climate change. A ready market for Eucalyptus products has motivated farmers to grow the species to improve their livelihoods through increased income. However, the extensive growth of eucalypts has generated controversy on high water use by the species and negative effects on soil fertility and biodiversity. Concerns have also been expressed about the adverse effects of growing eucalypts near water sources because of the observed drying of streams, rivers and springs. Nevertheless, farmers continue to grow Eucalyptus because of its fast growth and good economic returns. To address these concerns, the government has recently provided guidelines on growing Eucalyptus trees and is presently working on a policy to guide the growth of the species in Kenya. As a third government effort, this booklet presents important facts on the growing and use of Eucalyptus in Kenya. The booklet will contribute to the effective growth of Eucalyptus with minimum adverse effects on the environment, leading to increased forest cover, carbon storage and renewable energy, improved livelihood and creating wealth for the citizens.
Keywords: Forestry; Kenya